Abitare Approcci interdisciplinari e nuove prospettive - Boi, Luciano; Cannas, Andrea; Vargiu, Luca (La biblioteca di Medea, 2019)
Dwelling can be conceived as making sense of a portion of space or as a condition of possibility of human existence; besides, there exist innumerable situations d'habiter, that is, the particular modalities with which human groups settle in specific places or with which individuals organise their lives. In any case, as dwelling precisely involves the very essence of mankind, it constitutes a crossroads in which various fields of knowledge and several practices enter in a dialogue, up to the point of re-discussing their status on different levels, from the anthropological one to the more specifically methodological or procedural one. The contributions of this volume try to reflect on the meaning of dwelling, involving philosophical and architectural discourse, historical and ethno-anthropological investigation, the contributions of geography, the artistic experience and the literary and cinematographic horizons.